Computed Tomographic Findings of Eosinophilic Enteritis in Eight Cats: Case Series - Toshiyuki Tanaka; Hana Tsuruta; Koudai Furukawa; Hideo Akiyoshi (Veterinary Medicine and Science)
ABSTRACT In cats, eosinophilic enteritis (EE) is diagnosed when eosinophils are the predominant inflammatory cells on histopathology and no underlying trigger for their presence can be identified. Gastrointestinal eosinophilic sclerosing fibroplasia is a unique fibroblastic response of EE. Contrast‐enhanced computed tomography (CT) facilitates the objective characterisation of intestinal lesions and associated pathology. To the best of our knowledge, there are no reports of CT findings in cats with EE. This case series retrospectively evaluated the CT findings of eight cats with EE including lesion location, intestinal wall layering structure, mass formation, location and size of lymph nodes, total wall thickness and outer intestinal layer relative thickness. The development of a layered intestinal wall appearance in the early and delayed phases was detected in seven (87.5%) and five cases (62.5%), respectively. All patients exhibited intestinal wall thickening, seven (87.5%) with marked thickening of the outer intestinal wall. Lesions were diffuse in all cats, involving the duodenum, jejunum and ileum in seven cats (87.5%) and in the ileum and colon in one cat (12.5%). Mass formation and lymphadenomegaly was detected in one (12.5%) and four cats (50%), respectively. The CT features of EE included thickening of the outer intestinal layer with development of a layered wall appearance and associated lymphadenomegaly.